If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (p + 3) + 9 = 3(p + -2) + 6 Reorder the terms: (3 + p) + 9 = 3(p + -2) + 6 Remove parenthesis around (3 + p) 3 + p + 9 = 3(p + -2) + 6 Reorder the terms: 3 + 9 + p = 3(p + -2) + 6 Combine like terms: 3 + 9 = 12 12 + p = 3(p + -2) + 6 Reorder the terms: 12 + p = 3(-2 + p) + 6 12 + p = (-2 * 3 + p * 3) + 6 12 + p = (-6 + 3p) + 6 Reorder the terms: 12 + p = -6 + 6 + 3p Combine like terms: -6 + 6 = 0 12 + p = 0 + 3p 12 + p = 3p Solving 12 + p = 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 12 + p + -3p = 3p + -3p Combine like terms: p + -3p = -2p 12 + -2p = 3p + -3p Combine like terms: 3p + -3p = 0 12 + -2p = 0 Add '-12' to each side of the equation. 12 + -12 + -2p = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -2p = 0 + -12 -2p = 0 + -12 Combine like terms: 0 + -12 = -12 -2p = -12 Divide each side by '-2'. p = 6 Simplifying p = 6
| 2(7a+4b)=6(10a+9b) | | 4a^2-a-3= | | -2(k+7)=16-8k | | 3+5y-(-4)=-17-y | | 3x-7=2x-Y+x+7 | | 1.5x+0.6=13.5 | | -2x-5=3x+20 | | 2(x+4)+3=2x+3 | | 6x-7=-4(x+6)+17 | | 2x-10=3x-11 | | -133=-10n-3 | | 3x+.9=18 | | 12b(6+8)=b-2(13-b)-7 | | 4(y+5)+3= | | -(-9k-9)+3(5+3k)=-5k-k | | a^2+36=100 | | X-16=34 | | -5L+4-4L+6=-17 | | 1=-5x-2 | | 125=2.5t | | 12s-7=8 | | x/3-x+4/7=2 | | 12(x-3)=-4-8 | | 4.99+0.65x=6.94 | | 19+7a=1-(6+a) | | 2x+19=23 | | 17(x+2)(x-5)=0 | | .5m+6.4=4.9-4 | | 4x-5=-50-5x | | 4x-(3x+2)+9=12-5x | | 19+1a=1-(6+a) | | -10-d=-34-5d |